Pengaruh Lingkungan Sosial terhadap Efektifitas Implementasi Kebijakan Rencana Tata Ruang Wilayah - Asep Sumaryana (JIANA ( Jurnal Ilmu Administrasi Negara ), 2011)
The research’s title is The Influence Of Social Environment on Implementation Effective-ness of Spatial Utilization Planning (RTRW) in Bandung City (A Study on Spatial Utilization inNorth Bandung Area)”. RTRW should be a guidance on regulating spatial utilization. In fact, NorthBandung area, which supposed to be a water conservation has be changed with more developingof building. This condition has influenced of social environment and task environment. To analyzeto all problem above, Structural Equation Modeling (SEM) analysis is used . this research also useinterview method with intellectual, practices and local population. The result shows that theinfluence of social environment in implementation effectiveness of RTRW in Bandung City issignificant. That means a conservation or devastation is depended with two environment aspect.With positive influence from, sustainable spatial utilization should be better. But, if the influence isnegative, spatial will be more devastated. Increasing physical development shows a negative influ-ence, so RTRW not protected maximally. In social environment, there are two dominant aspect:population and nature resources. Growth of Bandung residence population push spatial needsuntil this resources experience damaged